Inhibition of Coagulation Factor Xa Improves Myocardial Function During CVB3‐Induced Myocarditis. Issue 3 (June 2014) - Malz, Ronny; Weithauser, Alice; Tschöpe, Carsten; Schultheiss, Heinz‐Peter; Rauch, Ursula
Summary Introduction Myocarditis is induced by coxsackievirus B3 (CVB3). Myocardial inflammation is tied to the activation of coagulation. Coagulation factor (F) Xa, a central player in coagulation, activates matrix metalloproteinases (MMP), which modulate the remodeling. Aims In this study, we investigated the effects of pharmacological FXa inhibition on myocardial function, inflammation, and remodeling during a CVB3‐induced myocarditis. Methods and Results Immune cells and matrix proteins were detected by immunohistochemistry. The expression of cytokines was measured by real‐time PCR and the activity of MMP‐2 by zymography. Left ventricular function was analyzed using microconductance pressure catheter. Treatment with the FXa inhibitor fondaparinux led to an improved left ventricular function in CVB3‐induced mice compared to saline‐treated controls (dPdtmax: fondaparinux 4632 ± 499.6 vs. saline 3131 ± 374.0 [mmHg/s], P = 0.0503; SV: fondaparinux 33.19 ± 4.893 vs. saline 19.32 ± 2.236 [μL], P < 0.118; CO: fondaparinux 15124 ± 2183 vs. saline 8088 ± 1035 [μL/min], P < 0.05). Therapy with fondaparinux reduced the activity of MMP‐2 (fondaparinux 1.208 ± 0.1247 vs. saline 1.565 ± 0.05476, P < 0.05). The collagen type I/III ratio as well as the expression of TIMP‐1 was comparable in both infection groups postinfectionem (p.i.), despite an increased infiltration of macrophages into the hearts of mice treated with fondaparinux 8 days p.i. (CD68+: fondaparinux 494.2 ± 64.73 vs. saline 306.9 ± 43.73 [cells/mm2], P < 0.05). Anti‐inflammatory CD206‐positive M2‐type macrophages were increased in the infected hearts after fondaparinux treatment (CD206+: fondaparinux 182.1 ± 18.18 vs. saline 111.6 ± 21.07 [cells/mm2], P < 0.05), whereas CD80‐positive M1‐type macrophages were comparable in both groups. Conclusion In conclusion, selective inhibition of FXa improves the left ventricular function during CVB3‐induced myocarditis and seems to be associated with an improved myocardial remodeling.